Distribution of weedy rice escape variants in Clearfield rice production system - Jaafar, Nurul Farahidayu; Juraimi, Abdul Shukor; Ahmad Hamdani, Muhammad Saiful; Kamal, Md. Uddin; Man, Azmi (Gaurav Publications, 2014)
Weedy rice is made up of the undesirable biotypes of rice with early and easy shattering characteristics, which causes a major yield reduction in direct-seeded rice in Malaysia. Thus, a series of survey were conducted in the selected Clearfield rice fields in the four townships, namely, Kampung Sungai Manik, FELCRA Seberang Perak, Kampung Mampas and Kampung Sungai Mati in the Peninsular Malaysia from April 2012 and April 2013 to study the dominance and abundance of weedy rice escaping Clearfield Production System (known as weedy rice escape). The survey was done according to the quantitative survey method by using standardized quadrat. A total of 1240 and 813 weedy rice escapes in dry/off season 2012 and main season 2012 were identified in all surveyed rice fields, respectively. Kampung Mampas indicated the highest dominance of weedy rice escapes, while FELCRA Seberang Perak recorded the lowest dominance in both the planting seasons. From the farmers’ complaint, poor rice management and weeding practices were the major factors that contributed to weedy rice escape in the fields.